Adsorption and barrier properties of yaziv mine bentonite as material for landfill liners - Петрова, Маріанна Анатоліївна; Постнікова, Марія Олександрівна; Степова, Катерина Вікторівна (Eastern-European Journal of Enterprise Technologies, 2014)
The properties of natural bentonite clay of Yaziv mine (Lviv region., Ukraine) as a material for landfill liners and solid household and industrial waste storages were investigated. Copper and ammonium were selected as components that imitate the filtrate composition. Filtration coefficient, which is 10.9 m/s was experimentally found. Based on the porosity analysis, it was determined that the mineral belongs to the microporous materials with an average pore radius of 5Å. It was revealed that bentonite is able to irreversibly absorb large amounts of copper by the ion exchange mechanism. The full capacity of the mineral by copper is 115 mg/g. Ammonium adsorption proceeds according to the physical adsorption mechanism; maximum adsorption capacity is 0.175 mg/g. Saturation of the adsorbent is reached on the first day due to the high specific surface area. Remobilization ability of components when applying different desorbing agents was examined. The data obtained suggest that the adsorption ability of bentonite clay liners is not enough to ensure the environmental safety of ground and surface waters. Barriers, made of several materials with low permeability, different porosity, specific surface area and high adsorption ability of the filtrate components must be used.